Preclinical evaluation of immunogenicity, efficacy and safety of a recombinant plant-based SARS-CoV-2 RBD vaccine formulated with 3M-052-Alum adjuvant. Issue 17 (24th April 2023) - Phoolcharoen, Waranyoo; Shanmugaraj, Balamurugan; Khorattanakulchai, Narach; Sunyakumthorn, Piyanate; Pichyangkul, Sathit; Taepavarapruk, Pornnarin; Praserthsee, Wanlapa; Malaivijitnond, Suchinda; Manopwisedjaroen, Suwimon; Thitithanyanont, Arunee; Srisutthisamphan, Kanjana; Jongkaewwattana, Anan; et al.
Abstract: Cost-effective, and accessible vaccines are needed for mass immunization to control the ongoing coronavirus disease 2019 (COVID-19), especially in low- and middle-income countries (LMIC). A plant-based vaccine is an attractive technology platform since the recombinant proteins can be easily produced at large scale and low cost. For the recombinant subunit-based vaccines, effective adjuvants are crucial to enhance the magnitude and breadth of immune responses elicited by the vaccine. In this study, we report a preclinical evaluation of the immunogenicity, efficacy and safety of a recombinant plant-based SARS-CoV-2 RBD vaccine formulated with 3M-052 (TLR7/8 agonist)-Alum adjuvant. This vaccine formulation, named Baiya SARS-CoV-2 Vax 2, induced significant levels of RBD-specific IgG and neutralizing antibody responses in mice. A viral challenge study using humanized K18-hACE2 mice has shown that animals vaccinated with two doses of Baiya SARS-CoV-2 Vax 2 established immune protection against SARS-CoV-2. A study in nonhuman primates (cynomolgus monkeys) indicated that immunization with two doses of Baiya SARS-CoV-2 Vax 2 was safe, well tolerated, and induced neutralizing antibodies against the prototype virus and other viral variants (Alpha, Beta, Gamma, Delta, and Omicron subvariants). The toxicity of Baiya SARS-CoV-2 Vax 2 was further investigated in Jcl:SD rats, which demonstrated that a single dose and repeated doses of Baiya SARS-CoV-2 Vax 2 were well tolerated and no mortality or unanticipated findings were observed. Overall, these preclinical findings support further clinical development of Baiya SARS-CoV-2 Vax 2.